FEATURES OF THE REORGANIZATION OF UKRAINIAN SMALL-SCALE SCHOOLS IN MODERN CONDITIONS - Sitkar , Victor; Sitkar , Stepan (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The article highlights the peculiarities of the reorganization of Ukrainian small-capacity schools in the current conditions. It is emphasized that such educational institutions traditionally perform not only an educational function, but also serve as cultural centers of communities, a place of socialization and the formation of local identity. The decision to stop funding small-capacity schools is one of many steps towards reforming the education system. But whether this step will be a positive shift or will exacerbate the problems of inequality - only time and the ability of local authorities to adapt to new conditions will tell. In Ternopil region, from September 2025, 32 schools will fall under the scope of the resolution. This is not the largest indicator. In particular, in the neighboring Lviv region, as many as 54 educational institutions are planned to be closed. It is noted that despite economic challenges, full access to quality education remains one of the key rights of citizens guaranteed by the Constitution. Therefore, it is important to find balanced solutions that will take into account both the need to improve the quality of education and the need to ensure its accessibility for all students, regardless of their place of residence.